2019
DOI: 10.5530/ijper.53.3s.117
|View full text |Cite
|
Sign up to set email alerts
|

In-silico Designing, Synthesis, SAR and Microbiological Evaluation of Novel Amide Derivatives of 2-(3-methylbenzo[b]thiophen-6-yl)-1- (3-nitrophenyl)-1H-benzo[d]imidazole-5-carboxylic Acid

Abstract: Aim/Background: Due to this increasing problem of antibiotic resistance, the number of different antibiotics available is dwindling and there are only a handful of new antibiotics in the drug development pipeline. Therefore, there is an urgent need for the development of new antimicrobial drugs. In the present study, we have synthesized and investigated antimicrobial activities of novel derivatives with molecular docking studies. Methods: In this article, amide derivatives of 2-imidazole-5-carboxylic acid were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In 2019, Tanuj Hooda, Sunil Sharma, Naveen Goyal (Uttarakhand Technical University, India) synthesized Imidazole derivatives from carboxylic acid and evaluated the antibacterial activity against B.subtilis, S.aureus, P.aeruginosa, E.color, T.thermophilus by in vitro dilution method. It was identified that three compounds have the bactericidal effect against these bacteria [20]. [1,3,4]thiadiazole derivatives, such as antimicrobial activity, had been comprehensively studied.…”
Section: Antibacterial Effectmentioning
confidence: 99%
“…In 2019, Tanuj Hooda, Sunil Sharma, Naveen Goyal (Uttarakhand Technical University, India) synthesized Imidazole derivatives from carboxylic acid and evaluated the antibacterial activity against B.subtilis, S.aureus, P.aeruginosa, E.color, T.thermophilus by in vitro dilution method. It was identified that three compounds have the bactericidal effect against these bacteria [20]. [1,3,4]thiadiazole derivatives, such as antimicrobial activity, had been comprehensively studied.…”
Section: Antibacterial Effectmentioning
confidence: 99%